Kajian terhadap Persepsi Mahasiswa terhadap Rasisme dalam Konteks Sila Kedua Pancasila : Studi di Jurusan PPKn Unimed - Agustin Pratama Sihotang; Deo Agung Haganta Barus; Eirene Dahlia Sidabutar; Joy Prana Bangun; Nasywa Yasmin Purba; Ramsul Yandi Nababan (Universitas Maritim AMNI Semarang, 2024)
Pancasila is the basis of the state that has been in effect since June 1, 1945. Pancasila is not only the basis of the state, but Pancasila is the personality of the Indoneisa nation. After that the life of the nation and the nation of the Indonesian people is regulated and adjusted by Pancasila. In the second principle, which reads